Biological causes of immunogenic cancer cell death (ICD) and anti-tumor therapy; Combination of Oncolytic virus-based immunotherapy and CAR T-cell therapy for ICD induction - Amirhossein Mardi; Anastasia V. Shirokova; Rebar N. Mohammed; Ali Keshavarz; Angelina Olegovna Zekiy; Lakshmi Thangavelu; Talar Ahmad Merza Mohammad; Faroogh Marofi; Navid Shomali; Amir Zamani; Morteza Akbari (2022)
Abstract Chimeric antigen receptor (CAR) T-cell therapy is a promising and rapidly expanding therapeutic option for a wide range of human malignancies. Despite the ongoing progress of CAR T-cell therapy in hematologic malignancies, the application of this therapeutic strategy in solid tumors has encountered several challenges due to antigen heterogeneity, suboptimal CAR T-cell trafficking, and the immunosuppressive features of the tumor microenvironment (TME). Oncolytic virotherapy is a novel cancer therapy that employs competent or genetically modified oncolytic viruses (OVs) to preferentially proliferate in tumor cells. OVs in combination with CAR T-cells are promising candidates for overcoming the current drawbacks of CAR T-cell application in tumors through triggering immunogenic cell death (ICD) in cancer cells. ICD is a type of cellular death in which danger-associated molecular patterns (DAMPs) and tumor-specific antigens are released, leading to the stimulation of potent anti-cancer immunity. In the present review, we discuss the biological causes of ICD, different types of ICD, and the synergistic combination of OVs and CAR T-cells to reach potent tumor-specific immunity.